Taqiyyah as a Behavioral Method in Islamic Education: Comparison of Agreement and Disagreement Opinions - Esmat Ramezani Mashkani (Comparative Education Society of Iran ( CESIR), 2021)
Taqiyyah means expressing or concealing one's belief and action against one's heart to avoid religious or worldly harm is one of the jurisprudential issues that has educational consequences. The purpose of this study is to investigate Taqiyyah as a behavioral method in Islamic education by applying the pros and cons from both jurisprudential and educational aspects. The method of the present study is a qualitatively comparative with an analytical-inferential approach. Researchers have used the library method to collect data, including the study of primary and secondary sources. To analyze the data, the qualitative analysis method was used based on data recording and categorization of the "subject" unit. Findings of research in the field of jurisprudence show that Shiite jurists were mainly in favor of Taqiyyah and Sunni scholars were against it. From the educational point of view, Taqiyyah means positive in the sense of self-control and tolerance with people whose beliefs are not in line with one's beliefs. The main similarity between the proponents and opponents of Taqiyyah is the recourse of both groups to the verses of the Qur'an and the behavior of the Prophet Mohammad and his companions through the presentation of different interpretations. Another finding of the research shows that according to the proponents, in many matters of life, it is not necessary to refer to Taqiyyah and it cannot be referred to as a permanent behavioral principle. According to the opponents of Taqiyyah, in the contemporary world and due to the new developments based on the prevalence of legal mechanisms in society, resorting to Taqiyyah is not necessary. The similarity between the two groups of proponents and opponents of Taqiyyah is the attention to positive developments such as civil rights and negative developments such as the increase of religious extremism to accept or reject Taqiyyah.